Becoming aware of cinematic techniques in propaganda: Instructional support by cueing and training. (October 2015) - Merkt, Martin; Sochatzy, Florian
Abstract: Cinematic techniques are used to induce biased interpretations of historical videos. Therefore, awareness of these techniques is necessary when working with videos as historical sources. Two studies investigated the effects of training and cueing on the analysis of propaganda. Whereas training benefitted the identification and interpretation of cinematic techniques in propaganda, cueing cinematic techniques on a category level (e.g., camera angle) resulted in less specific analyses with regard to identifying the techniques and hardly affected the interpretation of the techniques' effects. In contrast, more specific manifestation cues (e.g., low angle shot) resulted in more specific analyses and positively affected giving correct interpretations of the cinematic techniques' effects. Interestingly, the effects of cueing were not just observed for practice clips, which included cues, but transferred to test clips, which did not include cues. Overall, these studies constitute a starting point for investigating the effects of cueing on the analysis of propaganda. Highlights: Awareness of cinematic techniques is necessary to analyze historical video sources. Training improved identification and interpretation of cinematic techniques. Category cues led to less specific analyses and hardly affected interpretation. Manifestation cues improved identification and interpretation of techniques. Effects of cueing transferred to test clips, that did not include cues.